The Effect Of Carbon Accounting Implementation On Financial And Environmental Performance: An Empirical Study On Companies That Go Public - Maf'ul Taufik (Penerbit Jurnal Indonesia, 2025)
This study aims to analyze the influence of carbon accounting implementation on financial and environmental performance in companies that go public in Indonesia. Carbon accounting is a mechanism for measuring, reporting, and managing carbon emissions that is adopted in response to increasing awareness of environmental sustainability. Using a quantitative approach, this study analyzes secondary data in the form of sustainability reports and annual reports from companies listed on the Indonesia Stock Exchange (IDX) for the 2019-2023 period. Financial performance is measured through profitability, cost efficiency, and market value indicators, while environmental performance is evaluated based on carbon emission reduction and compliance with environmental regulations. The results show that the implementation of carbon accounting has a positive effect on financial performance through better operational efficiency and company reputation. In addition, there is a significant impact on environmental performance in the form of reduced carbon emissions and increased compliance with sustainability standards. This study provides practical implications for companies to be more proactive in adopting carbon accounting practices to achieve a balance between financial goals and environmental responsibility. This research also encourages policymakers to strengthen regulations related to carbon accounting in supporting sustainable economic development.